Study of serum C-peptide levels in newly diagnosed diabetic mellitus subjects of North Gujarat region of India - Pathan, Rashidkhan B.; Purohit, Niravkumar H.; Choudhary, Prema Ram (International Journal of Advances in Medicine, 2022)
Background: Serum C-peptide has appeared as the chief clinical and practically adequate marker of β-cell function of pancreas. Serum insulin and C-peptide are concomitantly secreted into the blood circulation in equal amount. The aim of the study was to determine serum C-peptide levels in newly diagnosed diabetic mellitus subjects of North Gujarat region of India. Methods:The present cross-sectional study was done on 50 subjects of recently diagnosed Diabetes mellitus (T2DM) and non-diabetic healthy controls at Banas Medical College and our trust-based hospital. All diabetics patients were further classified into two groups; normal FC group consist of subjects with FC level 0.5-3.2 ng/ml (N=14) and high FC group included subjects with FC>3.2 ng/ml (N=36). The patients’ demographic and anthropometric parameters were recorded; detailed history and clinical examination were performed in the entire cases. All biochemical parameters were analyzed. Results: Predominance of the T2DM subjects was in the age group of 41-50 years. Mean value for age (p<0.01), anthropometric (p<0.01), fasting plasma glucose (p<0.001), HbA1c (p<0.01), cholesterol (p<0.01), triglycerides (p<0.001) and C-peptide (p<0.001) were significantly higher in the T2DM subjects. The mean values of fasting plasma glucose (p<0.001) and HbA1c (p<0.01) are significantly higher in T2DM subject with high C-peptide level as compared to normal C-peptide level. Conclusions:In our study, we conclude that elevated levels of fasting C-peptide in newly diagnosed T2DM. Therefore, we suggested that serum C-peptide levels are valuable as marker of endogenous insulin production from β-cell of pancreas.